2019
DOI: 10.3390/cells8091053
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Effects on Non-Alcoholic Fatty Liver Disease Are Related to MicroRNA-34a-5p/Sirt1 Axis and Autophagy

Abstract: Melatonin, an indole produced by pineal and extrapineal tissues, but also taken with a vegetarian diet, has strong anti-oxidant, anti-inflammatory and anti-obesogenic potentials. Non-alcoholic fatty liver disease (NAFLD) is the hepatic side of the metabolic syndrome. NAFLD is a still reversible phase but may evolve into steatohepatitis (NASH), cirrhosis and carcinoma. Currently, an effective therapy for blocking NAFLD staging is lacking. Silent information regulator 1 (SIRT1), a NAD+ dependent histone deacetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 89 publications
(97 reference statements)
2
52
0
Order By: Relevance
“…Silent information regulator 1 (SIRT1), an NAD + dependent histone deacetylase, regulated energy and lipid homeostasis in the liver, and miR-34a-5p was the direct inhibitor of SIRT1. Melatonin reversed HFD-caused liver fibrosis and NAFLD by increasing the ratio of LC3-II/I, decreasing cytoplasmic p62 levels and reducing the expression of miR-34a-5p in WT, but not SIRT1 heterozygous (HET) mice 64 . Similar to previous results, the activation of autophagy by rapamycin alleviated methionine choline-deficient (MCD) diet-caused liver fibrosis in a NASH mouse model 65 .…”
Section: Liver Fibrosis and Autophagymentioning
confidence: 99%
“…Silent information regulator 1 (SIRT1), an NAD + dependent histone deacetylase, regulated energy and lipid homeostasis in the liver, and miR-34a-5p was the direct inhibitor of SIRT1. Melatonin reversed HFD-caused liver fibrosis and NAFLD by increasing the ratio of LC3-II/I, decreasing cytoplasmic p62 levels and reducing the expression of miR-34a-5p in WT, but not SIRT1 heterozygous (HET) mice 64 . Similar to previous results, the activation of autophagy by rapamycin alleviated methionine choline-deficient (MCD) diet-caused liver fibrosis in a NASH mouse model 65 .…”
Section: Liver Fibrosis and Autophagymentioning
confidence: 99%
“…Pterostilbene, a resveratrol analogue found in edible berries, downregulates miR-34a overexpression in fructose fed rats, leading to the restoration of SIRT1 activity and the inhibition of SREBP-1 lipogenic activity [ 100 ]. Melatonin is naturally found in edible plants and may be responsible for lower expression of miR-34a in melatonin-treated HFD-fed mice, along with higher SIRT1 and lower SREBP-1 activities [ 101 ]. Finally, the novel carnosic acid decreases miR-34a overexpression, alleviates dyslipidemia and activates the anti-apoptotic properties of SIRT1 in rats submitted to a HFD [ 102 ].…”
Section: Diet-derived Compounds As Antioxidant Defense Through Mirmentioning
confidence: 99%
“…8 Accumulating evidence suggests important links between the regulation of autophagy and liver complications associated with obesity and NAFLD. [9][10][11] In particular, a previous study of the drug liraglutide indicated that the promotion of autophagy can ameliorate the effects of NAFLD via the SIRT1/SIRT3-FOXO3a pathway. 10 The autophagy process is dependent on a multitude of signaling pathways.…”
Section: Introductionmentioning
confidence: 99%